2022
DOI: 10.3390/ijms232415808
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis: An Indicator of COVID-19 Severity in Critically Ill Patients

Abstract: Here, we examined the dynamics of the gut and respiratory microbiomes in severe COVID-19 patients in need of mechanical ventilation in the intensive care unit (ICU). We recruited 85 critically ill patients (53 with COVID-19 and 32 without COVID-19) and 17 healthy controls (HCs) and monitored them for up to 4 weeks. We analyzed the bacterial and fungal taxonomic profiles and loads of 232 gut and respiratory samples and we measured the blood levels of Interleukin 6, IgG, and IgM in COVID-19 patients. Upon ICU ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Interestingly, it has been estimated that 40–45% of CoV-2 cases are asymptomatic, which raises the question of which biological factors are present in the asymptomatic group that contribute to this limited symptomology and prevention of disease [ 8 ]. One of the host factors that is key to pathology from a viral infection is the correlation observed between gut dysbiosis and disease, which established a protective role of metabolic byproducts including the short-chain fatty acid (SCFA) acetate [ 9 , 10 ]. Recent work has shown that SCFAs produced from the gut microbiota significantly reduced the expression of ACE2 in airway epithelial cells in culture, which could also help, in part, explain the discrepancy in symptoms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been estimated that 40–45% of CoV-2 cases are asymptomatic, which raises the question of which biological factors are present in the asymptomatic group that contribute to this limited symptomology and prevention of disease [ 8 ]. One of the host factors that is key to pathology from a viral infection is the correlation observed between gut dysbiosis and disease, which established a protective role of metabolic byproducts including the short-chain fatty acid (SCFA) acetate [ 9 , 10 ]. Recent work has shown that SCFAs produced from the gut microbiota significantly reduced the expression of ACE2 in airway epithelial cells in culture, which could also help, in part, explain the discrepancy in symptoms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%